Kinerja jati asal Muna pada plot uji klon jati di empat lokasi - Hamdan Adma Adinugraha; Budi Leksono (Jurnal Penelitian Kehutanan Wallacea, 2013)
The research was conducted to evaluate the growth of teak clone (Tectona grandis L.f.) taken from land race population at Muna Island in South East Sulawesi. The trials were planted in 2002 – 2005 in 4 locations as follows: Kemampo (South Sumatera), Kotabaru (South Kalimantan), Gunung Kidul (Yogyakarta) and Wonogiri (Central Java). The growth of teak clones from Muna at 5 years old in 4 locations was as followed: the average of total height (9,98 m, 13,11 m, 7,46 m and 9,37m), diameter/DBH (11,09 cm, 12,80 cm, 7,87 cm and 13,24 cm) and tree volume estimation (0,0624 m3 , 0,117 m3 , 0,028 m3 and 0,099 m3 ). The growth performances of teak clone from Muna were stable at middle position in all locations. The best growth was gained in Kotabaru and the lowest in in Gunung Kidul